Cleavable carbosilane dendrimers modulate the thermodynamical properties of DMPC/DPPG lipid membrane and conformation of human serum albumin - Paulina Rycharska; Sylwia Michlewska; Adam Buczkowski; Małgorzata Grygiel; Judith Recio-Ruiz; Sandra García-Gallego; Francisco Javier de la Mata; Maria Bryszewska; Janusz Blasiak; Maksim Ionov (Chemistry and Physics of Lipids, 2026)

Red wine (poly)phenols supplementation reduces amyloid-beta (aβ) pathology in APP/PS1 mice model: Possible implications of gut-brain axis explored by untargeted fecal metabolomics - Juana I. Mosele; Jose Ignacio Manzano; Sandrith Paola Sampayo-Rodríguez; María Iñiguez; Emma Recio-Fernández; Silvia Yuste; Patricia Pérez Matute; Maria-Jose Motilva (Food Research International, 2025)

Cyclosporin A-loaded dissolving microneedles for dermatitis therapy: Development, characterisation and efficacy in a delayed-type hypersensitivity in vivo model - Miquel Martínez-Navarrete; Antonio José Guillot; Maria C. Lobita; María Carmen Recio; Rosa Giner; Juan Aparicio-Blanco; María Carmen Montesinos; Hélder A. Santos; Ana Melero (Drug Delivery and Translational Research, 2024)
Several drugs can be used for treating inflammatory skin pathologies like dermatitis and psoriasis. However, for the management of chronic and long-term cases, topical administration is preferred over oral delivery since it prevents certain issues due to systemic side effects from occurring. Cyclosporin A (CsA) has been used for this purpose; however, its high molecular weight (1202 Da) restricts the diffusion through the skin structure. Here, we developed a nano-in-micro device combining lipid vesicles (LVs) and dissolving microneedle array patches (DMAPs) for targeted skin delivery. CsA-LVs allowed the effective incorporation of CsA in the hydrophilic DMAP matrix despite the hydrophobicity of the drug. Polymeric matrix composed of poly (vinyl alcohol) (5% w/v), poly (vinyl pyrrolidine) (15% w/v) and CsA-LV dispersion (10% v/v) led to the formation of CsA-LVs@DMAPs with adequate mechanical properties to penetrate the stratum corneum barrier. The safety and biocompatibility were ensured in an in vitro viability test using HaCaT keratinocytes and L929 fibroblast cell lines. Ex vivo permeability studies in a Franz-diffusion cell setup showed effective drug retention in the skin structure. Finally, CsA-LVs@DMAPs were challenged in an in vivo murine model of delayed-type hypersensitivity to corroborate their potential to ameliorate skin inflammatory conditions. Different findings like photon emission reduction in bioluminescence study, normalisation of histological damage and decrease of inflammatory cytokines point out the effectivity of CsA-LVs@DMAPs to treat these conditions. Overall, our study demonstrates that CsA-LVs@DMAPs can downregulate the skin inflammatory environment which paves the way for their clinical translation and their use as an alternative to corticosteroid-based therapies. Graphical Abstract

Isolation and Differentiation of Neurons and Glial Cells from Olfactory Epithelium in Living Subjects - Paula Unzueta-Larrinaga; Rocío Barrena-Barbadillo; Inés Ibarra-Lecue; Igor Horrillo; Aitor Villate; Maria Recio; J. Javier Meana; Rebeca Diez-Alarcia; Oihane Mentxaka; Rafael Segarra; Nestor Etxebarria; Luis F. Callado; et al. (Molecular Neurobiology, 2023)
The study of psychiatric and neurological diseases requires the substrate in which the disorders occur, that is, the nervous tissue. Currently, several types of human bio-specimens are being used for research, including postmortem brains, cerebrospinal fluid, induced pluripotent stem (iPS) cells, and induced neuronal (iN) cells. However, these samples are far from providing a useful predictive, diagnostic, or prognostic biomarker. The olfactory epithelium is a region close to the brain that has received increased interest as a research tool for the study of brain mechanisms in complex neuropsychiatric and neurological diseases. The olfactory sensory neurons are replaced by neurogenesis throughout adult life from stem cells on the basement membrane. These stem cells are multipotent and can be propagated in neurospheres, proliferated in vitro and differentiated into multiple cell types including neurons and glia. For all these reasons, olfactory epithelium provides a unique resource for investigating neuronal molecular markers of neuropsychiatric and neurological diseases. Here, we describe the isolation and culture of human differentiated neurons and glial cells from olfactory epithelium of living subjects by an easy and non-invasive exfoliation method that may serve as a useful tool for the research in brain diseases.

Comparing minimum number of individuals and abundance from non-invasive DNA sampling and camera trapping in the red fox (Vulpes vulpes) - Sara Martin-Garcia; Maria Cortazar-Chinarro; Mariano Rodríguez-Recio; José Jiménez; Jacob Höglund; Emilio Virgós (Biodiversity and Conservation, 2023)
Applying the most appropriate sampling method is essential for estimating population size. Sampling methods and techniques to estimate abundance may be limited by environmental characteristics, species traits, specific requirements of the techniques, or the economic resources to carry out the sampling. Thus, evaluating multiple sampling methods in monitoring populations is essential for establishing effective conservation strategies. In this study, we compare two of the most commonly used sampling methods with the red fox ( Vulpes vulpes ) as the type species. On the one hand, we compared the minimum number of individuals (NI) detected by camera trapping, identifying individuals by morphological characteristics with the minimum number of individuals detected by DNA faeces and a set of 16 microsatellites. On the other hand, we estimated abundance by performing an N-mixture model using information from camera-traps to study the relationship between abundance and the minimum number of individuals detected. Results showed that the minimum NI provided by camera trapping was slightly higher than that of DNA faecal genotyping, with 23.66 and 19 individuals, respectively. In addition, abundance and NI detected by camera trapping showed a positive relationship. In contrast, there was a non-significant negative relationship between NI detected by faecal DNA and abundance estimates. Our results suggest using the minimum number of photo-identified individuals as a reliable index to study variation in red fox abundance when other advanced methods cannot be implemented in the study of population size. However, it is necessary to improve the methods of faecal sampling to study the relationship with camera-trap data.

Sulfate removal from mine-impacted water by electrocoagulation: statistical study, factorial design, and kinetics - Caroline Rodrigues; Hioná V. Dal Magro Follmann; Dámaris Núñez-Gómez; Maria Eliza Nagel-Hassemer; Flávio R. Lapolli; María Ángeles Lobo-Recio (Environmental Science and Pollution Research, 2020)

Comparative study on treatment performance, membrane fouling, and microbial community profile between conventional and hybrid sequencing batch membrane bioreactors for municipal wastewater treatment - Rayra Emanuelly da Costa; Maria Angeles Lobo-Recio; André Aguiar Battistelli; João Paulo Bassin; Tiago José Belli; Flávio Rubens Lapolli (Environmental Science and Pollution Research, 2018)

Molecular topology: a strategy to identify novel compounds against ulcerative colitis - María Gálvez-Llompart; Maria C. Recio; Ramón García-Domenech; Jorge Gálvez (Molecular Diversity, 2017)

MiR-205 is downregulated in hereditary hemorrhagic telangiectasia and impairs TGF-beta signaling pathways in endothelial cells - Sebastien P. Tabruyn; Sylvain Hansen; Maria-Luisa Ojeda-Fernández; Nicolas Bovy; Roberto Zarrabeitia; Lucia Recio-Poveda; Carmelo Bernabéu; Joseph A. Martial; Luisa-Maria Botella; Ingrid Struman (Angiogenesis, 2013)

Arsenic Mining Waste in the Catchment Area of the Madrid Detrital Aquifer (Spain) - Lorena Recio-Vazquez; Javier Garcia-Guinea; Pilar Carral; Ana Maria Alvarez; Fernando Garrido (Water, Air, & Soil Pollution, 2011)

Transcription and weak expression of HLA-DRB6 : a gene with anomalies in exon 1 and other regions. - Victor M. Fernandez-Soria; Pablo Morales; Maria J. Castro; Belen Suarez; Maria J. Recio; Miguel A. Moreno; Estela Paz-Artal; A. Arnaiz-Villena (Immunogenetics, 1998)

Primate Mhc-E and -G alleles - Antonio Arnaiz-Villena; Jorge Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1998)

Primate Mhc-E and -G alleles - A. Arnaiz-Villena; J. Martinez-Laso; Miguel Alvarez; Maria J. Castro; Pilar Varela; Eduardo Gomez-Casado; Belen Suarez; María José Recio; Gilberto Vargas-Alarcón; Pablo Morales (Immunogenetics, 1997)

Periglacial features of the Subbetic Mountains of southern Spain (Córdoba Province) - Maria Luisa Torres-Giron; Jose Manuel Recio-Espejo (Journal of Quaternary Science, 1997)

Periglacial features of the Subbetic Mountains of southern Spain (Córdoba Province) - Maria Luisa Torres‐Giron; Jose Manuel Recio‐Espejo (Journal of Quaternary Science, 1997)

Annual, daily and diurnal variations of Urticaceae airborne pollen in Málaga (Spain) - Maria del Mar Trigo; Baltasar Cabezudo; Marta Recio; Francisco Javier Toro (Aerobiologia, 1996)

Annual, daily and dirunal variations of Urticaceae airborne pollen in Málaga (Spain) - Maria del Mar Trigo; Baltasar Cabezudo; Marta Recio; Francisco Javier Toro (Aerobiologia, 1996)